Investigation of gas flow through soils and granular fill materials for the optimisation of radon soil depressurisation systems. (March 2019) - Fuente, Marta; Muñoz, Eduardo; Sicilia, Isabel; Goggins, Jamie; Hung, Le Chi; Frutos, Borja; Foley, Mark
Abstract: The purpose of this study is to investigate gas flow through different types of granular fill materials and soil by means of a series of experimental laboratory tests, in relation to soil depressurisation systems for radon reduction under buildings and the soil surrounding the foundation. Gas permeability characterisation of materials used as granular fill material beneath the slab in buildings is a key parameter for the optimum performance of soil depressurisation systems to mitigate radon. A test apparatus was developed, adapted from previous studies, to measure the gas permeability of the samples and Finite Element Method numerical simulations were validated to simulate the flow behaviour through them. Theoretical expressions for permeability were discussed based on the analysis of experimental results and numerical simulations, finding that Darcy-Forchheimer equation provides the best match to the experimental results. Darcy's law also proved to be suitable for low gas velocities, whereas Ergun's equation resulted in a poor fit of the experimental data. Benchmark analysis of the granular fill materials under study and other European standards (Spanish, Irish and British) is also presented. Highlights: Development of apparatus to test permeability of granular fill materials and soil. Theoretical equations for gas permeability were discussed. Finite Element Method simulations were performed. Benchmarking analysis of European standard granular fill materials was conducted.